TRADITIONAL GAME OF ULAR NAGA FOR EARLY CHILDHOOD DEVELOPMENT FROM TEACHER’S PERSPECTIVE - Pramudyani, Avanti Vera Risti (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2020)
The traditional game is a cultural activity contain not only cultural values but also as methods to create joyful learning. One of the traditional games that famous at Early Childhood Education is Ular Naga. Games of Ular Naga is a traditional game from Yogyakarta, Indonesia with specific activities such as singing, playing, dan dialogue. Within have some various activities and complicated this game can develop many aspects of early childhood. This study aims to know the benefit of traditional games of Ular Naga for early childhood teacher perspective in early childhood education. This research is qualitative research with early childhood teacher as the subject and to collecting the data with the interview, observation, and documentation. Validation data used triangulation technique. Analysis of data such as collected data, reduction data, display data and make a conclusion. The result shows that the majority of the teacher's perspective has the same argument that Ular Naga has the benefit of developing an aspect of the children such as gross motor skills with activities walking, running, catching, make a train, and make a line and social-emotional aspects with activities build cooperative within friends in the group. However the teacher not yet explanation holistically all the aspect that should be can develop from Ular Naga.